Supplier fixed costs and retail market monopolization - Stéphane Caprice; Vanessa von Schlippenbach; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Considering a vertical structure with perfectly competitive upstream firms that deliver a homogenous good to a differentiated retail duopoly, we show that upstream fixed costs may help to monopolize the downstream market. We find that downstream prices increase in upstream firms' fixed costs when both intra- and interbrand competition exist. Our findings contradict the common wisdom that fixed costs do not affect market outcomes.
Keywords: L13; L14; L42; 330; Fixed Costs; Vertical Contracting; Monopolization